A Rare Case of Immature Sacrococcygeal Teratoma With Lymph Node Metastasis in a Neonate. Issue 8 (November 2021) - Masahata, Kazunori; Ichikawa, Chihiro; Higuchi, Kohei; Makino, Katsutoshi; Abe, Takatoshi; Kim, Kiyokazu; Yamamichi, Taku; Tayama, Ai; Soh, Hideki; Usui, Noriaki
Abstract : This is the first report of an immature sacrococcygeal teratoma with inguinal lymph node metastasis, providing the histologic transformation of an immature teratoma in association with chemotherapy. Incomplete tumor resection with coccygectomy was performed, and the histopathologic diagnosis was a grade 3 immature teratoma. Following the initial surgery, the residual tumors enlarged and the tumors metastasized to the inguinal lymph node, demonstrating immature teratoma without yolk sac tumor components. Although the tumor markers normalized after chemotherapy, the residual tumors had enlarged significantly. Therefore, a complete resection of the residual tumors was performed, and they were found to be mature teratomas.